2013
DOI: 10.1108/17542431311327646
|View full text |Cite
|
Sign up to set email alerts
|

Designing appropriate valuation model for sustainable property tax system in developing countries

Abstract: PurposeThis study seeks to contrive a sustainable valuation model for developing countries: a model that reasonably combines simplicity with equity, cost effectiveness, transparency, and the peculiarities of the local market place for improved revenue yields.Design/methodology/approachThe study draws from theory, experiences of other nations and international best practices to arrive at what should be the most appropriate tax base, valuation basis, valuation method, and the most expedient valuation approach fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
1
21
0
2
Order By: Relevance
“…The factors have also been identified in the emerging property markets of Malaysia, Zambia and Tanzania (Kelly & Musunu, 2000;Nasir, 2006;Achu, 2013;Munshifwa et al, 2016). Moreover, the factors identified in this study are in agreement with some of the factors identified in studies such as Akinjare et al (2013), Babawale (2013), Atilola (2013), Effiong (2015) and Adegoke (2016) in Nigeria on other purposes of valuation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The factors have also been identified in the emerging property markets of Malaysia, Zambia and Tanzania (Kelly & Musunu, 2000;Nasir, 2006;Achu, 2013;Munshifwa et al, 2016). Moreover, the factors identified in this study are in agreement with some of the factors identified in studies such as Akinjare et al (2013), Babawale (2013), Atilola (2013), Effiong (2015) and Adegoke (2016) in Nigeria on other purposes of valuation.…”
Section: Discussionsupporting
confidence: 90%
“…It was concluded that lack of quality control and sanctions for wrong assessment could be attributed to the lapses observed in the 1993 assessment. Other studies that have commented on the likely causes of variance in property tax assessment are by Babawale and Nubi (2011), Oni and Ajayi (2011), Atilola (2013) and Babawale (2013). These authors attributed the causes of variance in rateable values to non-robustness of the law in terms of its comprehensiveness and explicitness.…”
Section: Factors Causing Variance In Property Valuationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been argued that the strength of a property-based tax is dependent on the robustness of the valuation system (Babawale, 2013). According to Bahl and Martinez-Vazquez (2007), the valuation of property is one of the key problems with effective use of property tax in developing countries.…”
Section: Valuation and Classification Of Properties And Businessesmentioning
confidence: 99%
“…The ability of property taxation and business licensing to generate sufficient revenues for local governments depends largely on the valuation and classification of properties and businesses. It has also been argued that the strength of a property-based tax is dependent on the robustness of the valuation system (Babawale, 2013). According to Bahl and Martinez-Vazquez (2007), the valuation of property is one of the key problems with effective use of property tax in developing countries.…”
Section: Valuation and Classification Of Properties And Businessesmentioning
confidence: 99%